Prince Paku Ningrat’s Qur’an Manuscript at the Sumenep Palace in 1793: Its Characteristics and Analysis - Moh Syakur; Rafdi Dhiya Ulhaq (The Institute of Research and Service Community IPMAFA Pati, 2022)
This article examines the Qur'anic manuscripts written by Prince Paku Ningrat in 1793 at the Sumenep Palace. Through a philological approach, it aims to know the history and characteristics of the manuscripts. This study found the characteristics of philology in Islamic studies through the characteristics of the Qur'anic manuscripts. There are several patterns that make the Mushaf stand out, such as the illumination on the Mushaf, which is beautiful and full of Madura culture. The use of Rasm script, punctuation, Tajweed and Waqf are characteristics of 18th 18th-century scripts from the post-modern era that are different from modern manuscripts.